Design and Simulation of a 12-Cavity Injection Mold with Optimized Runner System for Efficient Production of Sample Cups - Budiyantoro, Cahyo; Pratama, Wahyu Aji (JMPM (Jurnal Material dan Proses Manufaktur), 2024)
Injection molding is widely used in large-scale manufacturing due to its efficiency in producing plastic products. One such product is the sample cup, used in the medical field for liquid sample storage. An inefficient runner system in injection molding can cause uneven material distribution, leading to defects and material waste. This study aims to simulate the injection molding process for a 12-cavity mold, optimizing the runner system and designing a three-plate mold for sample cup production. Product and mold designs were created using Autodesk Inventor Professional, and injection molding simulations were performed using Moldflow Plastic Insight to determine the optimal runner layout. The simulation results indicated that runner layout 1 was superior, with improved performance in terms of fill time (0.8028 s), pressure at switchover (85.93), sink index (0.4359%), volumetric shrinkage (10.50%), and cycle time (50 s). Based on these results, layout 1 was selected for the three-plate mold.